Sustainable Architecture Using Solar Cells in Libya - Ahmad Al-Ajwad, Omar Bilfageh, Manssour Bin Miskeen , Mohamed Wali Sharief (Journal of Pure & Applied Sciences, 2020)
The close connection between the environment and sustainable development led to the emergence of a concept of development called sustainable, which requires attention to environmental protection, and renewable energy is one of the means to protect the environment, so we find many countries now developing this source of energy and setting it as a goal that it seeks to achieve, especially in the field of construction. Solar energy is the largest and most important source of renewable energies, and solar cells are the non-thermal method by which electricity is generated from solar energy directly when added to the building, as all the electrical energy needs of the building can be covered, but there is a problem in separating it from aesthetics and relationships Architectural configuration, as a tool for generating energy, is added to the building without plastic value, This research concerned with that research problem, and that the research aims to study the extent to which architectural shaping is achieved using solar cells by applying solar cells according to the plastic rules and clarifying the extent to which they can be combined with buildings to achieve the various methods and relationships of architectural formation in order to be dealt with by the architects as a formative element that achieves harmony and harmony. Along with the rest of the structural elements, in addition to the basic role which is generating electric energy from renewable sources - solar energy - which by achieving it can be considered sustainable architectural formation. This was done through the methodology suggested by the research using the descriptive analysis method and the creation of a questionnaire to extrapolate the architects’ views of the use of the solar cell system and its effect on the architectural formation and work on applying strategies to encourage its use. This research concluded that the solar cell system is an essential architectural element in the building that achieves the goals of sustainable architecture in terms of function, beauty, durability and economy.